Cerebrospinal Fluid Cell-Free DNA-Based Detection of High Level of Genomic Instability Is Associated With Poor Prognosis in NSCLC Patients With Leptomeningeal Metastases - Wu, Xi; Xing, Puyuan; Shi, Min; Guo, Weihua; Zhao, Fangping; Zhu, Honglin; Xiao, Jianping; Wan, Jinghai; Li, Junling (Frontiers in Oncology, 2022)
Introduction: Leptomeningeal metastases (LM) commonly occurs in non-small cell lung cancer (NSCLC) patients and has a dismal prognosis. Due to limited access to leptomeningeal lesions, the genetic characteristic of LM has not be well studied now. Cerebrospinal fluid (CSF) may be the most representative liquid biopsy to get genomic information from LM in NSCLC. Methods: The CSF biopsies and matched peripheral blood biopsies were collected from 33 NSCLC patients with LM. We profiled the genetic alterations from LM using CSF cell-free DNA (cfDNA) and compared it to plasma cfDNA. Somatic mutations were examined using targeted sequencing. Genomic instability was analysis with low coverage whole genome sequencing. Results: The driver mutations were detected in 100% of CSF cfDNA with much higher variant allele frequency, compared 57.5% in matched plasma cfDNA. Furtherly, we found that proportions of CSF cfDNA fragments below 150 bp were significantly higher than ones in plasma cfDNA. These indicated enrichment of circulating tumor DNA (ctDNA) in CSF and explained for high sensitivity of mutation detection in CSF. The absence of some mutations in CSF cfDNA, especially first/second-generation EGFR TKIs resistant mutation T790M, which were present in plasma cfDNA samples, indicates different mechanisms of cancer evolution between LM and extracranial lesions. In addition, 86.6% of CSF ctDNA samples revealed high levels of genomic instability, compared to 2.5% in plasma cfDNA samples. A higher number of large-scale state transitions (LSTs) in CSF cfDNA, was associated with a shorter OS. Conclusion: Our results suggested LM and extracranial lesion developed independently. Both CSF cfDNA and plasma cfDNA genetic profiling are necessary to make clinical decisions for NSCLC patients with LM. Through CSF based low coverage WGS, a high level of LSTs was identified as a potential biomarker for poor prognosis.